1961
DOI: 10.1139/v61-004
|View full text |Cite
|
Sign up to set email alerts
|

The Donor Characteristics of the Carbonyl: Group:ii. The Effect of Angular Variations at the Carbonyl Group

Abstract: The effect of variations in the angle X-C-X' (in a typical carbonyl compound XXIC=O) on the carbonyl stretching frequency (PC-0) is examined in the light of recently published empirical relations between vc ,o and the ionization potential. INTRODUCTIONIn a recent paper dealing with the donor characteristics of the carbonyl group (1) empirical relationships were demonstrated between the carbonyl stretching frequency (vc=,) and the ionization potential (IP). Two classes of compounds were noted: those having no g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1963
1963
1999
1999

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…(Susz has recently summarized (8) the results of carbonyl shifts in various complexes of ketones with Lewis acids, and found that the shift, Av, for the same Lewis acid increased in the series acetone < 4-heptanone < acetophenone < benzophenone. This is in the order of decreasing carbonyl frequency, ionization potential, and therefore increasing donor ability (7,9).) There are a few irregularities in the shifts that one particular Lewis acid generates with different donors.…”
Section: Discussionmentioning
confidence: 99%
“…(Susz has recently summarized (8) the results of carbonyl shifts in various complexes of ketones with Lewis acids, and found that the shift, Av, for the same Lewis acid increased in the series acetone < 4-heptanone < acetophenone < benzophenone. This is in the order of decreasing carbonyl frequency, ionization potential, and therefore increasing donor ability (7,9).) There are a few irregularities in the shifts that one particular Lewis acid generates with different donors.…”
Section: Discussionmentioning
confidence: 99%
“…The circumstances leading to enhanced basicity in carbonyl groups have been discussed in detail (2,3). T h e y-pyrones satisfy most of the required conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the results of various theoretical methods like AM1, 12 PM3 13 and B3LYP, 14-16 the first ionization potential is assigned to the removal of an electron from the nitrogen lone-pair MO, n(N), and the second IP is assigned to the analogous process related to the n(O) orbital. Compared with other tertiary lactams, the first IP of 20 appears at an unusually low energy, about 0.6 eV lower than in 1-methylpiperidin-2-one (9). The n(N) ionization of 20 is, however, 0.36 eV higher than that of 1-azaadamantane (21).…”
Section: Pe Spectrum and Electronic Structure Of Azaadamantanone 20mentioning
confidence: 89%
“…In this way a value of 9.00 eV is obtained for IP[n(O)] which compares well to that found experimentally (Table 1). for various secondary and tertiary lactams (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). Azaadamantanone 20 has a carbonyl frequency of 1732 cm Ϫ1 11 from which ν 120 (C᎐ ᎐ O) = 1716.4 cm Ϫ1 is obtained by eqn.…”
Section: Pe Spectrum and Electronic Structure Of Azaadamantanone 20mentioning
confidence: 99%